Penggunaan Media Kartu Kosakata pada Latihan Membaca bagi Pemelajar Asing di Sekolah Darul Muhmin Thailand - Fani, Mulyana Mei; Febriyana, Mutia (Universitas Muhammadiyah Surabaya, 2025)
ABSTRACT The purpose of this study was to analyze effectiveness the use of vocabulary flashcard of reading practice for foreign learners at Darul Muhmin School, Thailand. This study uses a qualitative approach with descriptive methods with the research subject of class 6-3 at Darul Muhmin School with a total of 19 students. Data collection techniques consisted of observation, tests, and interviews. This research was conducted for two weeks, on the first week students practiced reading without using vocabulary flashcard and the second week student using vocabulary flashcard. The results show that the use of vocabulary flashcard can be applied to reading practice is one of the new alternative in BIPA learning. Students become active and make learning interesting. Keyword: bahasa Indonesia teaching, reading skills, vocabulary flashcard, BIPA